Lynch syndrome: clinical, pathological, and genetic insights - Schneider, Ralph; Kloor, Matthias (Langenbeck's archives of surgery, 2012)
Introduction: Lynch syndrome as the most common hereditary colorectal cancer syndrome and the most common cause of hereditary endometrial cancer is characterized by an autosomal dominant inheritance with a penetrance of 85-90%. The molecular genetic underlying mechanism is a mutation in one of the mismatch repair genes.MethodsIn order to identify patients with Lynch syndrome, a nuclear family history should be ascertained and matched with the Amsterdam criteria. A different approach for identification is the adherence to Bethesda criteria and subsequent testing for microsatellite instability. In patients with unstable tumors as an indicator for mismatch repair deficiency, genetic counseling and mutation analysis are warranted. For families fulfilling the Amsterdam criteria, intensified screening is recommended, even if a pathogenic mutation is not identified.ResultsIndividuals from families with a proven pathogenic mutation that are tested negative are at normal population risk for cancers and may be dismissed from intensified surveillance. Prophylactic surgery in high-risk individuals without neoplasia is not generally recommended. At the time of a colon primary, however, extended surgery should be discussed in the light of a high rate of metachronous cancers. The worries of impairing functional results have now been evaluated in the light of quality of life in a large international cohort. Interestingly, extended (prophylactic) surgery does not lead to inferior quality of life with equal perioperative risks.ConclusionsTherefore, taking the risk reduction into account, extended surgery at the time of the first colon primary should at least be discussed, if not recommended. Also, prophylactic hysterectomy and bilateral oophorectomy at the time of a colorectal primary should be recommended if family planning has been completed.
Published online: 24 February 2012
Gesehen am 29.06.2018